672 Isolated pulmonic valve endocarditis. AN unusual case with giant vegetations detected by transthoracic echocardiography. (8th December 2021) - Parato, Vito Maurizio; Di Geso, Luca; Parato, Andrea Giovanni; Pelliccioni, Simona
Abstract: Aims: Isolated pulmonic valve infective endocarditis (PV-IE) is a rare form of endocarditis. Methods and results: The authors report a case of giant vegetations detected by transthoracic echocardiography on pulmonic valve in a 33 year-old patient, with drug abuse history (Figure 1 ). Patient underwent surgical intervention by pulmonary valved bioconduit implantation. After operation a pulmonary embolism episode was treated by a direct oral anticoagulant. The final outcome was favourable. We report a short review of this rare pathology. Conclusions: The difficulty in diagnosing PV-IE is due to inability to properly visualize the pulmonic valve by echocardiography. In this case, with such large vegetations, transthoracic echocardiography (TTE) allowed a correct diagnosis and an effective surgical planning, confirming its importance as diagnostic tool.